Potamocarcinus colombiensis sp. nov.: Un nuevo cangrejo de agua dulce (Decapoda: Brachyura: Pseudothelphusidae) de la Serranía Costera del Baudo, Colombia - von Prahl, Henry (1987)
A new species of Potamocarcinus from the Serrania del Baudo, Colombia is deseribed. It differs from Potamocarcinus richmondi (Rathbun) by the shape and position of the cephalie teeth and by the marginal process of the gonopod. This is the first report of the genus Potamocarcinus for Colombia.